Detecting the signature of permafrost thaw in Arctic rivers. Issue 8 (27th April 2015) - Spencer, Robert G. M.; Mann, Paul J.; Dittmar, Thorsten; Eglinton, Timothy I.; McIntyre, Cameron; Holmes, R. Max; Zimov, Nikita; Stubbins, Aron
Abstract Climate change induced permafrost thaw in the Arctic is mobilizing ancient dissolved organic carbon (DOC) into headwater streams; however, DOC exported from the mouth of major arctic rivers appears predominantly modern. Here we highlight that ancient (>20, 000 years B.P.) permafrost DOC is rapidly utilized by microbes ( 50% DOC loss in <7 days) and that permafrost DOC decay rates (0.12 to 0.19 day−1) exceed those for DOC in a major arctic river (Kolyma: 0.09 day−1). Permafrost DOC exhibited unique molecular signatures, including high levels of aliphatics that were rapidly utilized by microbes. As microbes processed permafrost DOC, its distinctive chemical signatures were degraded and converged toward those of DOC in the Kolyma River. The extreme biolability of permafrost DOC and the rapid loss of its distinct molecular signature may explain the apparent contradiction between observed permafrost DOC release to headwaters and the lack of a permafrost signal in DOC exported via major arctic rivers to the ocean.